2013
DOI: 10.1155/2013/805467
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Axonal Diversity in Molecular Layer Heterotopia of the Rat Cerebellar Vermis

Abstract: Molecular layer heterotopia of the cerebellar primary fissure are a characteristic of many rat strains and are hypothesized to result from defect of granule cells exiting the external granule cell layer during cerebellar development. However, the cellular and axonal constituents of these malformations remain poorly understood. In the present report, we use histochemistry and immunocytochemistry to identify neuronal, glial, and axonal classes in molecular layer heterotopia. In particular, we identify parvalbumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…Consistent with a model of migration defect of granule cells as a primary cause of these malformations which we have termed, molecular layer heterotopia (MLH), our group and others have shown that Bergman glial cells expressing nestin [23] or glial fibrillary acidic protein [22] have disorganized radial fibers. Moreover, migrating granule cells expressing doublecortin were found to have abnormal migratory morphologies and polarity in areas with developing heterotopia [23]. Why heterotopia are only found along the primary fissure remains unknown.…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…Consistent with a model of migration defect of granule cells as a primary cause of these malformations which we have termed, molecular layer heterotopia (MLH), our group and others have shown that Bergman glial cells expressing nestin [23] or glial fibrillary acidic protein [22] have disorganized radial fibers. Moreover, migrating granule cells expressing doublecortin were found to have abnormal migratory morphologies and polarity in areas with developing heterotopia [23]. Why heterotopia are only found along the primary fissure remains unknown.…”
Section: Introductionsupporting
confidence: 79%
“…Remarkably, these malformations are almost exclusively found along the primary fissure in regions lacking pia and are characterized by granule cells present in the molecular layer that fail to migrate to the internal granule cell layer. Although other neuron and glial cell types are present in malformations [22], the overwhelming majority of cells present are granule cells expressing doublecortin [23] or alpha-6 ionotropic gammaaminobutyric acid receptors [22]. Consistent with a model of migration defect of granule cells as a primary cause of these malformations which we have termed, molecular layer heterotopia (MLH), our group and others have shown that Bergman glial cells expressing nestin [23] or glial fibrillary acidic protein [22] have disorganized radial fibers.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations